2020
DOI: 10.3390/molecules25245890
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Polymers via Radical Homopolymerization and Copolymerization of a Series of Terpenoid-Derived Conjugated Dienes with exo-Methylene and 6-Membered Ring

Abstract: A series of exo-methylene 6-membered ring conjugated dienes, which are directly or indirectly obtained from terpenoids, such as β-phellandrene, carvone, piperitone, and verbenone, were radically polymerized. Although their radical homopolymerizations were very slow, radical copolymerizations proceeded well with various common vinyl monomers, such as methyl acrylate (MA), acrylonitrile (AN), methyl methacrylate (MMA), and styrene (St), resulting in copolymers with comparable incorporation ratios of bio-based cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…The cationic homopolymerization of (-)-VnD proceeded quantitatively with all Lewis acids, including EtAlCl 2 , TiCl 4 , BF 3 •OEt 2 , and SnCl 4 , in a 1:1 mixture of toluene and CH 2 Cl 2 at -78 °C and resulted in homopolymers with relatively high molecular weights (M n > 25000), unlike its radical homopolymerization, which yielded only low molecular weight oligomers (M n < 1000). 41 In addition, the cationic polymerizations were almost instantaneous except for BF 3 •OEt 2 , indicating that the reactivity of (-)-VnD is extremely high despite the absence of electron-donating heteroatoms such as the oxygen in VEs. The poly((-)-VnD) obtained from all Lewis acid catalysts showed similar 1 H NMR spectra (Fig.…”
Section: Conventional Cationic Polymerization Of (-)-Vnd Ptd and (±)-Hcvdmentioning
confidence: 98%
See 3 more Smart Citations
“…The cationic homopolymerization of (-)-VnD proceeded quantitatively with all Lewis acids, including EtAlCl 2 , TiCl 4 , BF 3 •OEt 2 , and SnCl 4 , in a 1:1 mixture of toluene and CH 2 Cl 2 at -78 °C and resulted in homopolymers with relatively high molecular weights (M n > 25000), unlike its radical homopolymerization, which yielded only low molecular weight oligomers (M n < 1000). 41 In addition, the cationic polymerizations were almost instantaneous except for BF 3 •OEt 2 , indicating that the reactivity of (-)-VnD is extremely high despite the absence of electron-donating heteroatoms such as the oxygen in VEs. The poly((-)-VnD) obtained from all Lewis acid catalysts showed similar 1 H NMR spectra (Fig.…”
Section: Conventional Cationic Polymerization Of (-)-Vnd Ptd and (±)-Hcvdmentioning
confidence: 98%
“…Verbenone (enantiomeric pure (-)-form) and piperitone (mixture of enantiomers, predominantly (R)-(-)-form) were converted into exo-methylene-conjugated dienes, (-)-VnD (purity: >99%, [] D = -43.5°) and PtD (purity: 95%, [] D = +15.7°), respectively, by the Wittig reaction as reported previously. 41,42 Racemic (±)-HCvD ([] D = -1.9°) was prepared by mixing equimolar amounts of (+)-and (-)-HCvD, which were synthesized via selective hydrogenation of the pendant olefins in (+)-and (-)-carvone, respectively, followed by the Wittig reaction as reported. 28 These biobased compounds are all exomethylene-conjugated dienes with a 6-membered cyclohexenyl ring, whereas the position of the methyl group as the substituent reaction is different or 4-position (VnD and PtD) to the exo-methylene carbon in the conjugated diene).…”
Section: Synthesis Of Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 33–37 ] The polymer structure control for methyl methacrylate (MMA) and other many kinds of conjugated monomers were performed using trithiocarbonate compounds as the RAFT agent. [ 38–43 ] In many cases, however, it has been reported that the precise control of the living radical polymerization is interfered by polar and functional groups included in the methacrylate monomers, such as HEMA. [ 44–50 ] In this study, therefore, we synthesized PBHEMA with well‐controlled molecular weight, molecular weight distribution, and chain end groups as well as the block copolymers containing PBHEMA and the other polymethacrylate segments using the RAFT polymerization process using 4‐cyano‐4‐((dodecylsulfanylthiocarbonyl)sulfanyl)pentanoic acid (CDTPA) as the RAFT agent ( Figure ).…”
Section: Introductionmentioning
confidence: 99%